PENGARUH VOLUME KENDARAAN TERHADAP TINGKAT KERUSAKAN JALAN RUAS JALAN DARUL HIKMAH KOTA MATARAM - DAVIDRIANTO DADI; AMINULLAH AMINULLAH; NI MADE NIA BUNGA S.D.; BAIQ RENI SARI DEWI (SOSIAL SAINS DAN TEKNOLOGI, 2023)
The purpose of this study is to determine the effect of vehicle volume on the level of road damage. And Knowing the Types of Damage that occurred on Jalan Darul Hikmah, Mataram City. The type of research used is a survey research method. The results of this study are road damage (Nr) on Jalan Darul Hikmah by 33%. There is a relationship between the volume of the type of vehicle with a road damage value of 230.88%. The higher the Vehicle Volume, the greater the damage that will occur